2018
DOI: 10.1063/1.5040061
|View full text |Cite
|
Sign up to set email alerts
|

Optical modulation of coherent phonon emission in optomechanical cavities

Abstract: Optomechanical structures are well suited to study photon-phonon interactions, and they also turn out to be potential building blocks for phononic circuits and quantum computing. In phononic circuits, in which information is carried and processed by phonons, optomechanical structures could be used as interfaces to photons and electrons thanks to their excellent coupling efficiency. Among the components required for phononic circuits, such structures could be used to create coherent phonon sources and detectors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Finally, we explore the effect of illuminating the Master cavity region with a top heating laser. Our previous work on a single OMC showed that its dynamical state is modified when the laser is switched on because of photothermal effects [36]. Now, before switching on the top pumping, we set the parameters of the laser driving the Slave in a way that its dynamical state is a mechanical lasing regime at S activated by the 3 rd harmonic of the optical force [32].…”
Section: Activation/deactivation Of the Synchronized State With An Ex...mentioning
confidence: 99%
“…Finally, we explore the effect of illuminating the Master cavity region with a top heating laser. Our previous work on a single OMC showed that its dynamical state is modified when the laser is switched on because of photothermal effects [36]. Now, before switching on the top pumping, we set the parameters of the laser driving the Slave in a way that its dynamical state is a mechanical lasing regime at S activated by the 3 rd harmonic of the optical force [32].…”
Section: Activation/deactivation Of the Synchronized State With An Ex...mentioning
confidence: 99%
“…Another fundamental property of acoustic superlattices that has not been exploited here are the Bloch mode symmetries at the minigap edges. It has been shown [44] that an inversion of these symmetries can be achieved by closing and re-opening a minigap, inducing a topological phase transition and hence allowing the construction of topological interface states [23][24][25]45]. This approach could for example be combined with the adiabatic resonator presented in Fig.2, resulting in an additional confined state between the two modes of the well, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The complication in achieving this goal derives from the fact that the most common materials used in photonics, such as glass for fiber optics and silicon for integrated photonics, hardly change their optical properties, even under intense optical or electrical stimuli. For this reason, optical modulation and switching, and more generally tunability, are usually reached by means of free-carrier injection, chemical and mechanical activation, or by deploying materials with large electro-optic or optical nonlinear coefficients [ 3 , 4 , 5 , 6 , 7 ]. All these mechanisms are inherently weak and require intense control signals and long interaction lengths in order to produce significant optical modulation.…”
Section: Introductionmentioning
confidence: 99%